2018
DOI: 10.1080/15592324.2018.1460048
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and genotoxic damages in plants in response to heavy metal stress and maintenance of genome stability

Abstract: Plants, being sessile in nature, are constantly exposed to various environmental stresses, such as solar UV radiations, soil salinity, drought and desiccation, rehydration, low and high temperatures and other vast array of air and soil borne chemicals, industrial waste products, metals and metalloids. These agents, either directly or indirectly via the induction of oxidative stress and overproduction of reactive oxygen species (ROS), frequently perturb the chemical or physical structures of DNA and induce both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 207 publications
(207 reference statements)
1
60
0
Order By: Relevance
“…Protein-level oxidative damage has been suggested to hinder the detoxification process and reduce the plant tolerance to stress [ 57 , 59 ]. The exposure to NPs induced DNA damage [ 60 ], indicating possible genotoxic effects that could lead to cell death [ 53 , 54 ]. Here, we have observed that this oxidative stress could also lead to the formation of 8-oxo-guanine, one of the major mutagenic DNA damages that could significantly impair gene expression and function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein-level oxidative damage has been suggested to hinder the detoxification process and reduce the plant tolerance to stress [ 57 , 59 ]. The exposure to NPs induced DNA damage [ 60 ], indicating possible genotoxic effects that could lead to cell death [ 53 , 54 ]. Here, we have observed that this oxidative stress could also lead to the formation of 8-oxo-guanine, one of the major mutagenic DNA damages that could significantly impair gene expression and function.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant response to ROS scavenging is a means of avoiding potential oxidative damage caused by the application of NPs. To do so, plants developed a set of antioxidant defense systems that rely on enzymatic and/or non-enzymatic mechanisms [ 53 , 54 ]. Since ROS was often used by plants as a second messenger for the signal transduction of multiple physiological reactions, ROS cannot be completely scavenged.…”
Section: Resultsmentioning
confidence: 99%
“…Nouairi et al (2006) reported that the accumulation of Cd suppresses the growth of root and shoot in B. juncea and B. napus under cadmium stress. Further, Dutta et al (2018b) reported also reduced root growth and shoot lengths in B. juncea under different heavy metals, including cadmium. Similar results were reported by Pandey & Ripathi (2011) where Cd treatment has an inhibitory effect on the growth of Albizia proceraas roots.…”
Section: Discussionmentioning
confidence: 90%
“…The key mechanism in the protection and survival of plants under heavy metal stress is regulation of its gene expression (Dutta et al 2018b). YSL3 belongs to Oligopeptide transporter family (OPT), known to be involved in different processes nitrogen mobilization (Koh et al 2002, Stacey et al 2008, glutathione transport (Cagnac et al 2004, heavy metal sequestration (Vasconcelos et al 2008), and long-distance metal distribution (Stacey et al 2008).…”
mentioning
confidence: 99%
“…Transduction of heavy metal stress signaling is started by ion channels/receptors through awareness of stress signals and also through non-protein messengers like hydrogen ions, calcium and cyclic nucleotides as given in ( Figure 1 ). Several studies reported the importance of these signaling molecules and responsive genes in plants against the stress induced by HMs [ 56 , 57 , 58 , 59 , 60 ].…”
Section: Signaling Response In Plants Against Heavy Metal Stressmentioning
confidence: 99%